From asylum to prison deinstitutionalization and the rise of mass incarceration after 1945 - Parsons, Anne E. (Justice, power, and politics., 2018)
"Prisons and asylums developed in parallel in the United States as institutions dedicated to the quarantine, detention, and punishment of the socially marginal. A widely accepted popular narrative holds that deinstitutionalization from the 1950s to the 1990s diminished the role of asylums in America. Yet, as Anne E. Parsons reveals, the asylum did not die--in fact, many of its structures have been transformed into prisons, just as prisons have shifted to locking up those who in an earlier era would have been sent to an asylum"--